Równania Powłoki Stożkowej Trójwarstwowej Wewnątrz Użebrowanej z Lekka Warstwą Wypełniającą - J. Rutecki (Engineering Transactions, 1960)
Equations of equilibrium of three-layer conical shell are derived. After the determination of the displacement strains and stresses at any point of the shell the variational method is used thus obtaining a system of five equations. For a certain case of load, after the derivation of the AIRY function, a system of four partial differential equations is obtained, from which it is easy in the case of a cylindrical shell to pass to a system of two differential equations obtained by GRIGOLYUK and determining the stress function and the deflection function.